Firmicutes Dysbiosis After Chlorhexidine Prophylaxis in Healthy Patients Submitted to Impacted Lower Third Molar Extraction - Neves, Carlos Augusto das; Alves, Carlos Henrique; Rocha, Natália Conceição; Rizzardi, Karina Ferreira; Russi, Karolyne Larissa; Palazzi, Alexandre Augusto Albigiante; Parisotto, Thaís Manzano; Girardello, Raquel (Frontiers in Cellular and Infection Microbiology, 2021)
Prophylaxis with antiseptic and antibiotic therapy is common in impacted lower third molar surgeries, despite the lack of consensus among professionals and researchers in the indication for healthy patients. The aim of the present preliminary study was to verify the impact of prophylaxis therapy with antiseptic and antibiotic in healthy patients submitted to impacted lower third molar extraction, according to oral microorganism quantification. Eleven patients submitted to impacted lower third molar extraction, under prophylactic therapy with 0.12% chlorhexidine and amoxicillin in four experimental phases, were evaluated. Our results showed no significant reduction in total bacteria load, as well as in Bacteroidetes and C. albicans loads in the oral cavity, after prophylactic therapy with antiseptic and antibiotic. On the other hand, there was a significant difference between the Firmicutes levels across the follow-up, and this effect seems to be large (ηp²=0.94). Post-hoc test demonstrated that the levels of Firmicutes in T1 were higher than T0, T2, and T3, suggesting a microbiota dysbiosis, when 0.12% chlorhexidine use, which may be responsible for selection of antibiotic-resistant microorganisms. Our results alert for an overuse of antiseptic and antibiotics by dentists and for a better evaluation of the available protocols.